Cardissey: uma plataforma web para a produção de jogos de cartas com propósitos - Rodrigues, Delivelton Teixeira (2023)
The use of games in the teaching-learning process is already a reality in several educational institutions. The use of educational games, whether digital or non-digital, is able to promote, through ludic activities, a simulation, an experiment, as well as special experiences for both the student and the teacher. However, it is still difficult to obtain educational games capable of adapting to different types of cultural, disciplinary and educational realities. This is because the process of building a game with these characteristics is usually complex and time-consuming. In fact, as many teachers have interesting ideas for educational games, game development is generally not feasible, either due to lack of knowledge in development tools or lack of time to do them. In this sense, this dissertation presents the development of Cardissey, a web platform aimed at non-experienced users for building and running digital card games for educational purposes. It provides reusable resources and game rules capable of representing and controlling the gameplay of traditional card games, along with an interactive environment capable of being utilized by non-programmers in producing desired educational card games. The final version of the Cardissey platform was validated in development activities carried out by computer engineering students and high school teachers. As obtained results, Cardissey presented an interesting potential in the production of card games for educational purposes, and can be used in the production of games that can be applied both in physical and digital environments available in the classroom.